How to uphold standards of medical education in Nepal: Some recommendations - Baral, P (Kathmandu University Medical Journal, 2010)
DOI: 10.3126/kumj.v7i3.2747 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 328-329